The Effect of Work Motivation, Leadership and Work Discipline on the Performance of Employees at the North Sumatra Provincial Transport Agency - Asnita Asnita; Saimara A.M Sebayang; M. Chaerul Rizky (Journal of Management, Economic, and Accounting, 2026)
This study aims to examine the effect of work motivation, leadership, and work discipline on employee performance at the North Sumatra Provincial Department of Transportation. The study employs a quantitative approach using a survey method. This study employs a quantitative approach using a survey method. A total of 60 employees were selected as the research sample from a population of 145 employees through simple random sampling. Data were collected through the distribution of questionnaires and analyzed using IBM SPSS Statistics version 31.0.1.0 with multiple linear regression analysis techniques. The results indicate that work motivation and work discipline have a positive and significant effect on employee performance, while leadership does not have a significant partial effect. However, simultaneously, work motivation, leadership, and work discipline have a significant effect on employee performance. These findings suggest that improving work motivation and work discipline plays an important role in enhancing employee performance within government institutions.